A kind of colorful flashing glaze-polished brick and preparation method thereof
By optimizing the glaze formula and process in the preparation method of colorful flash polished glaze tiles, the problem of insufficient flash effect and prone to bending and warping in the existing technology is solved, and a strong colorful flash effect and high hardness anti-fouling performance are achieved.
Patent Information
- Application Number
- CN202510146765.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-11
AI Technical Summary
The existing colorful flash polished tiles are not obvious enough under light conditions, have a single color, and are prone to defects such as bending and warping, which affects the yield rate.
The preparation method of colorful flash polished glaze tiles is adopted. By adding high-temperature transparent dry particles, low-temperature transparent dry particles, zircon sand and base glaze to the colorful flash glaze, their expansion coefficient and chemical composition are adjusted to form crystals with five different refractive indices, enhancing the optical effect, and ensuring the expansion coefficient matching between the glaze layer and the body layer and the base glaze layer through optimization formula and process.
It achieves a strong colorful flash effect while ensuring the flatness of the glazed brick, and improves hardness and anti-fouling performance, avoids defects such as bending and warping, and improves the yield rate.
Smart Images

Figure CN119638493B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building ceramics, and in particular to a colorful flashing glaze-polished brick and a preparation method thereof. Background Art
[0002] In the vast world of the ceramic market, consumers' demands are becoming increasingly diversified and personalized. They not only pursue the practicality and durability of ceramic products, but also have high expectations for their artistic value and visual beauty. The change in consumer consumption concepts has led to unprecedented attention and favor of consumers for colorful glittering glazed tiles that can shine like stars under the illumination of lights.
[0003] At present, the main methods for preparing colorful glitter effect glazed tiles mainly include the following methods: (1) using crystalline particles to achieve colorful glitter effect, but the size of the crystalline particles is small, so that the glitter effect is not obvious under normal lighting conditions, and usually requires close illumination of spotlights to be observed, and the colorful glitter effect is poor; (2) introducing high temperature resistant glitter mica into the colorful glitter glaze layer. Although the above method can achieve the glitter effect, the types of glitter mica are extremely limited, and the colors are mainly golden and silver. The color is relatively single, which is difficult to meet the market demand for colorful glitter effect. In addition, the high temperature melt that forms the colorful glitter glaze layer has a certain corrosiveness, which can gradually erode the surface of the glitter mica, not only destroying the integrity of the mica crystal, but also causing its surface to become rough and uneven, thereby greatly reducing the glitter effect of the glitter mica; (3) by directly introducing zircon sand into the colorful glitter glaze layer, using zircon sand to achieve the glitter effect of the glaze layer, but the glitter effect of zircon sand itself is limited, resulting in limited colorful glitter of the glaze layer. In addition, the expansion coefficient of the green body layer in the prior art is generally (215~240)×10 -6 / ℃, the expansion coefficient of the base glaze layer is generally (220~250)×10 -6 / ℃, while the expansion coefficient of zircon sand is only 10×10 -6 / ℃, and in order to enhance the colorful sparkling effect, a large amount of zircon sand is usually needed to be added to the glaze, resulting in poor matching of the expansion coefficients between the colorful sparkling glaze layer and the body layer, as well as between the colorful sparkling glaze layer and the base glaze layer, making it easy for the glazed tiles to produce stress differences, increasing the risk of defects such as bending and warping in the glazed tiles, thereby affecting the yield rate.
[0004] In summary, due to differences in the selection of raw materials and preparation processes, the existing glazed tiles have poor colorful sparkle effects and are prone to technical problems such as bending and warping. Summary of the invention
[0005] The purpose of the present invention is to provide a colorful flashing glazed tile and a preparation method thereof, which can not only present a strong colorful flashing effect while ensuring the flatness of the glazed tile, but also has higher hardness and anti-fouling performance, so as to overcome the shortcomings of the prior art.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] A method for preparing a colorful flashing glazed tile comprises the following steps:
[0008] A. Prepare a ceramic blank, press the ceramic blank, and obtain a blank layer after drying; the expansion coefficient of the blank layer is (215-240)×10 -6 / ℃;
[0009] B. Applying the base glaze to obtain a base glaze layer; the expansion coefficient of the base glaze layer is (220-250)×10 -6 / ℃;
[0010] C. applying colorful glitter glaze to obtain a colorful glitter glaze layer;
[0011] Calculated by weight, the raw materials of the colorful flashing glaze include 10-50 parts of high-temperature transparent dry particles I, 10-50 parts of low-temperature transparent dry particles I, 5-10 parts of zircon sand and 10-50 parts of base glaze I;
[0012] The expansion coefficient of the base glaze I is (270-280)×10 -6 / ℃;
[0013] The low-temperature transparent dry particles I have an initial melting point of 900-950°C and an expansion coefficient of (210-220)×10 -6 / ℃;
[0014] The high temperature transparent dry particles I have an initial melting point of 1000-1080°C and an expansion coefficient of (225-235)×10 -6 / ℃;
[0015] The raw materials of the high temperature transparent dry particles I include flash dry particles I and flash dry particles II, and the chemical composition of the flash dry particles I includes yttrium trioxide, and the chemical composition of the flash dry particles II includes niobium pentoxide and tantalum pentoxide;
[0016] D. After drying, it is put into the kiln for firing, and after polishing, colorful and shiny glazed tiles are obtained.
[0017] Further, in step C, the chemical composition of the flash dry particles I includes, calculated by mass percentage, Al2O3 9.8-10.1%, SiO2 3.0-3.3%, CaO 4.2-4.35%, MgO 2.8-3%, K2O 1.2-1.3%, Na2O 0.05-0.1%, TiO2 1.5-1.8%, B2O3 0.1-0.2%, BaO 23.5-24%, Li2O 3.0-3.5%, SrO 10.2-10.6%, P2O5 18-18.6%, F 18.5-19% and Y2O3 1.2-1.5%;
[0018] Calculated by mass percentage, the chemical components of the flash dry particles II include Al2O3 0.02-0.05%, Fe2O3 0.01-0.03%, CaO 0.01-0.05%, K2O 3.3-3.6%, Na2O 0.02-0.05%, TiO2 27.5-27.8%, BaO 0.05-0.1%, Li2O 0.05-0.1%, P2O5 27.2-27.6%, W 10.5-11%, Nb2O5 29.5-30% and Ta2O5 0.1-0.3%.
[0019] Furthermore, in step C, the high temperature transparent dry particles I also include transparent frit I;
[0020] Calculated by weight, the raw materials of the high-temperature transparent dry particles I include 30 to 50 parts of transparent frit I, 2 to 5 parts of flash dry particles I and 2 to 8 parts of flash dry particles II;
[0021] Calculated by weight, the raw materials of the transparent frit I include 5-10 parts of kaolin, 0-5 parts of aluminum oxide, 5-15 parts of quartz, 20-45 parts of potassium-sodium feldspar, 3-7 parts of zinc oxide, 3-10 parts of strontium carbonate, 3-7 parts of barium carbonate and 0-2 parts of lithium mica.
[0022] Furthermore, in step C, calculated by weight, the raw materials of the low-temperature transparent dry particles I include 1 to 3 parts of kaolin, 5 to 7 parts of quartz, 20 to 45 parts of potassium-sodium feldspar, 6 to 13 parts of zinc oxide, 10 to 35 parts of sodium bicarbonate, 3 to 10 parts of strontium carbonate and 5 to 20 parts of lithium mica.
[0023] Furthermore, the method further comprises step E, and step E is before step C;
[0024] Step E specifically comprises: applying a flash strengthening glaze to obtain a flash strengthening glaze layer;
[0025] Calculated by weight, the raw materials of the flash enhancement glaze include high-temperature transparent dry particles II, low-temperature transparent dry particles II, zircon sand and base glaze II;
[0026] The initial melting point of the high-temperature transparent dry granules II is greater than the initial melting point of the low-temperature transparent dry granules II.
[0027] Further, in step E, the flash enhancement glaze includes 10 to 30 parts of high temperature transparent dry particles II, 10 to 30 parts of low temperature transparent dry particles II, 20 to 70 parts of zircon sand and 10 to 50 parts of base glaze II, calculated by weight;
[0028] The expansion coefficient of the base glaze II is (270-280)×10 -6 / ℃;
[0029] The high temperature transparent dry granules II have an initial melting point of 1000-1080°C and an expansion coefficient of (230-250)×10 -6 / ℃;
[0030] The low-temperature transparent dry granules II have an initial melting point of 900-950°C and an expansion coefficient of (205-220)×10 -6 / ℃.
[0031] Furthermore, in step C and step E, calculated by weight, the raw materials of the base glaze I and the base glaze II include 5-10 parts of raw kaolin, 3-7 parts of burned kaolin, 2-5 parts of burned zinc oxide, 1-10 parts of wollastonite, 2-7 parts of calcite, 1-5 parts of dolomite, 0-5 parts of burned talc, 1-9 parts of quartz and 0-6 parts of strontium carbonate.
[0032] Further, in step E, calculated by weight, the high-temperature transparent dry particles II include 1 to 7 parts of kaolin, 3 to 7 parts of aluminum oxide, 5 to 15 parts of quartz, 20 to 45 parts of potassium-sodium feldspar, 3 to 7 parts of zinc oxide, 0 to 10 parts of sodium bicarbonate, 3 to 10 parts of strontium carbonate, 0 to 7 parts of barium carbonate and 0 to 5 parts of lithium mica.
[0033] Furthermore, in step E, the low-temperature transparent dry particles II include 50 to 90 parts of transparent frit II and 10 to 50 parts of high-lead frit, calculated by weight;
[0034] Calculated by weight, the raw materials of the transparent frit II include 1-3 parts of kaolin, 0-1 parts of aluminum oxide, 3-7 parts of quartz, 20-45 parts of potassium-sodium feldspar, 3-7 parts of zinc oxide, 3-15 parts of sodium bicarbonate, 3-10 parts of strontium carbonate, 0-3 parts of barium carbonate and 2-7 parts of lithium mica;
[0035] Calculated by weight, the raw materials of the high-lead frit include 33 to 75 parts of lead oxide and 25 to 67 parts of quartz.
[0036] A colorful flashing glaze-polished tile is prepared by using the method for preparing the colorful flashing glaze-polished tile.
[0037] The technical solution provided by the present invention may include the following beneficial effects:
[0038] 1. The refractive index of yttrium trioxide is 1.8, the refractive index of niobium pentoxide is 2.3, and the refractive index of tantalum pentoxide is 2.4. At the same time, zircon sand can form cubic zirconium oxide crystals with a refractive index of 2.14 after high-temperature calcination, and the glassy components in the colorful flash glaze form a glass phase with a refractive index of 1.54 after calcination, so that the colorful flash glaze layer has five crystals with different refractive indices. When the incident light irradiates the surface of the colorful flash glaze layer, complex refraction, reflection and interference phenomena may occur. The above optical effects work together to make the colorful flash glaze layer present a strong colorful flash effect.
[0039] 2. The expansion coefficient of base glaze I is (270~280)×10 -6 / ℃, the expansion coefficient of high temperature transparent dry particles I is (225~235)×10 -6 / ℃, the expansion coefficient of low temperature transparent dry particles I is (210~220)×10 -6 / ℃, while the expansion coefficient of zircon sand is about 10×10 -6 / ℃, there are significant differences in expansion coefficients between base glaze I, high temperature transparent dry particles I, low temperature transparent dry particles I and zircon sand. During the calcination process of polished glaze tiles, the above differences lead to the formation of extremely fine microcracks along the grain boundaries in the crystal microstructure that are difficult to detect with the naked eye. When irradiated with light, the above microcracks work together with the diffuse reflection on the crystal grain boundaries to effectively improve the reflection performance of light, thereby enhancing the colorful flash effect of the polished glaze tiles.
[0040] 3. Based on the principle of producing colorful flashing effect, only 5 to 10 parts of zircon sand need to be added to obtain a strong colorful flashing effect, which effectively avoids the problem of mismatch in expansion coefficients between the colorful flashing glaze layer and the body layer and between the colorful flashing glaze layer and the base glaze layer caused by excessive addition of zircon sand, thereby overcoming the defects of bending and warping of glazed tiles and ensuring that the glazed tiles have excellent flatness.
[0041] 4. This technical solution specifically adds high temperature transparent dry particles I, low temperature transparent dry particles I and base glaze I with larger expansion coefficients to the colorful flash glaze, and limits the addition amount of high temperature transparent dry particles I, low temperature transparent dry particles I and base glaze I, so that the expansion coefficient of the colorful flash glaze layer is (180~210)×10 -6 / ℃ range, so that the expansion coefficients between the colorful glaze layer and the body layer and between the colorful glaze layer and the base glaze layer are highly matched, which is beneficial to ensure that the polished glaze tiles have excellent flatness. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a surface effect diagram of the glazed tile of Example 1 of the present invention. DETAILED DESCRIPTION
[0043] The present technical solution provides a method for preparing a colorful flashing glazed tile, comprising the following steps:
[0044] A. Prepare a ceramic blank, press the ceramic blank, and obtain a blank layer after drying; the expansion coefficient of the blank layer is (215-240)×10 -6 / ℃;
[0045] B. Applying the base glaze to obtain a base glaze layer; the expansion coefficient of the base glaze layer is (220-250)×10 -6 / ℃;
[0046] C. applying colorful glitter glaze to obtain a colorful glitter glaze layer;
[0047] Calculated by weight, the raw materials of the colorful flashing glaze include 10-50 parts of high-temperature transparent dry particles I, 10-50 parts of low-temperature transparent dry particles I, 5-10 parts of zircon sand and 10-50 parts of base glaze I;
[0048] The expansion coefficient of the base glaze I is (270-280)×10 -6 / ℃;
[0049] The low-temperature transparent dry particles I have an initial melting point of 900-950°C and an expansion coefficient of (210-220)×10 -6 / ℃;
[0050] The high temperature transparent dry particles I have an initial melting point of 1000-1080°C and an expansion coefficient of (225-235)×10 -6 / ℃;
[0051] The raw materials of the high temperature transparent dry particles I include flash dry particles I and flash dry particles II, and the chemical composition of the flash dry particles I includes yttrium trioxide, and the chemical composition of the flash dry particles II includes niobium pentoxide and tantalum pentoxide;
[0052] D. After drying, it is put into the kiln for firing, and after polishing, colorful and shiny glazed tiles are obtained.
[0053] In order to solve the technical problems of existing glazed tiles, such as poor flashing effect and easy bending and warping, this technical solution proposes a method for preparing colorful flashing glazed tiles, including four steps: A (preparing a body layer), B (applying a bottom glaze), C (applying a colorful flashing glaze) and D (firing in a kiln), and optimizing the types and performance parameters of the raw materials in the colorful flashing glaze formula, combined with the polishing process, it is beneficial to ensure the flatness of the glazed tiles, not only to present a strong colorful flashing effect on the surface of the glazed tiles, but also to make them have higher hardness and anti-fouling properties, and to have both decorative and practical properties to meet the use requirements. It should be noted that the body layer in this technical solution is formed by pressing and drying the conventional ceramic blanks in the ceramic field, and the bottom glaze layer is formed by applying the conventional bottom glaze in the ceramic field. The ceramic blanks and bottom glazes are not further described here.
[0054] Specifically, the raw materials of the colorful flash glaze in the technical solution include high-temperature transparent dry particles II, low-temperature transparent dry particles II, zircon sand and base glaze I. Among them, the raw materials of high-temperature transparent dry particles I include flash dry particles I and flash dry particles II, the chemical composition of flash dry particles I includes yttrium trioxide, and the chemical composition of flash dry particles II includes niobium pentoxide and tantalum pentoxide. Specifically, the refractive index of yttrium trioxide is 1.8, the refractive index of niobium pentoxide is 2.3, and the refractive index of tantalum pentoxide is 2.4. At the same time, zircon sand can form cubic zirconium oxide crystals with a refractive index of 2.14 after high-temperature calcination, and the glassy components in the colorful flash glaze form a glass phase with a refractive index of 1.54 after calcination, so that the colorful flash glaze layer has five crystals with different refractive indices. When the incident light irradiates the surface of the colorful flash glaze layer, complex refraction, reflection and interference phenomena may occur. The above optical effects work together to make the colorful flash glaze layer present a strong colorful flash effect.
[0055] In addition, cubic zirconia crystals, due to their high refractive index and special crystal structure, have a good scattering effect on incident light, which is also beneficial to enhancing the colorful glitter effect of the colorful glitter glaze layer.
[0056] Furthermore, the expansion coefficient of base glaze I is (270-280)×10 -6 / ℃, the expansion coefficient of high temperature transparent dry particles I is (225~235)×10 -6 / ℃, the expansion coefficient of low temperature transparent dry particles I is (210~220)×10 -6 / ℃, while the expansion coefficient of zircon sand is about 10×10 -6 / ℃, there are significant differences in expansion coefficients between base glaze I, high temperature transparent dry particles I, low temperature transparent dry particles I and zircon sand. During the calcination process of polished glaze tiles, the above differences lead to the formation of extremely fine microcracks along the grain boundaries in the crystal microstructure that are difficult to detect with the naked eye. When irradiated with light, the above microcracks work together with the diffuse reflection on the crystal grain boundaries to effectively improve the reflection performance of light, thereby enhancing the colorful flash effect of the polished glaze tiles.
[0057] In summary, the technical solution uses the different refractive indices and expansion coefficients of various raw materials, as well as the high refractive index and special crystal structure of cubic zirconia crystals to make the glazed tiles show a strong colorful flash effect. It should be noted that since the microcracks of the technical solution are extremely fine and difficult to observe with the naked eye, they will not affect the hardness and stain resistance of the glazed tiles.
[0058] Secondly, in the prior art, since the expansion coefficient of zircon sand is too small and the amount of zircon sand added to the colorful flash glaze is large, the expansion coefficient matching between the colorful flash glaze layer and the body layer and the base glaze layer is poor, making the glazed tiles prone to defects such as bending and warping, affecting the yield.
[0059] This technical solution is based on the principle of producing a colorful glittering effect, so that only 5 to 10 parts of zircon sand need to be added to obtain a strong colorful glittering effect, effectively avoiding the problem of mismatch in expansion coefficients between the colorful glittering glaze layer and the body layer and between the colorful glittering glaze layer and the base glaze layer caused by excessive addition of zircon sand, thereby overcoming the defects of glazed tiles such as bending and warping, and ensuring that the glazed tiles have excellent flatness.
[0060] In addition, the technical solution specifically adds high temperature transparent dry particles I, low temperature transparent dry particles I and base glaze I with a large expansion coefficient to the colorful flash glaze, and limits the addition amount of high temperature transparent dry particles I, low temperature transparent dry particles I and base glaze I, so that the expansion coefficient of the colorful flash glaze layer is (180~210)×10 -6 / ℃ range, so that the expansion coefficients between the colorful glaze layer and the body layer and between the colorful glaze layer and the base glaze layer are highly matched, which is beneficial to ensure that the polished glaze tiles have excellent flatness.
[0061] Furthermore, since the expansion coefficient of the colorful glaze layer is lower than that of the body layer, compressive stress is formed on the surface of the glazed tile after calcination. The above compressive stress not only effectively prevents the glazed tile from bending and warping, but also helps to ensure that the glazed tile has excellent flatness.
[0062] In summary, the technical solution achieves a higher flatness of the polished glazed tiles by combining high-temperature transparent dry particles I, low-temperature transparent dry particles I, zircon sand and base glaze I, and limiting the addition amounts of high-temperature transparent dry particles I, low-temperature transparent dry particles I, zircon sand and base glaze I, as well as the expansion coefficients of high-temperature transparent dry particles I, low-temperature transparent dry particles I and base glaze I.
[0063] Again, in the present technical scheme, the initial melting point of the high-temperature transparent dry particles I is 1000-1080°C, and the initial melting point of the low-temperature transparent dry particles I is 900-950°C. By adjusting the ratio of the above two transparent dry particles, the calcination temperature of the colorful iridescent glaze can be flexibly adjusted, thereby achieving the adjustability of the calcination temperature of the glazed tiles, providing greater flexibility and precision for production.
[0064] Finally, the addition of high-temperature transparent dry particles I, low-temperature transparent dry particles I, base glaze I and zircon sand in the colorful flash glaze gives the colorful flash glaze layer a higher hardness; in addition, the microcracks of the present technical solution are extremely fine and difficult to observe with the naked eye, which will not affect the hardness of the polished glazed tile. In addition, the expansion coefficient of the colorful flash glaze layer is lower than that of the body layer, and the compressive stress formed after calcination is also conducive to enhancing the strength and hardness of the polished glazed tile. That is, the present technical solution is conducive to ensuring the hardness of the polished glazed tile through the above-mentioned multi-faceted effects.
[0065] Furthermore, the addition of base glaze I improves the fluidity of the colorful iridescent glaze, allowing it to flow and spread more smoothly, which is conducive to ensuring the smoothness and fineness of the surface, thereby enhancing the anti-fouling performance of the glazed tiles. At the same time, after the polishing treatment, the tiny bumps on the surface of the glazed tiles are effectively refined, and the surface becomes smoother and more delicate, which is not only conducive to improving the aesthetics of the glazed tiles, but also significantly enhances its anti-fouling performance. That is, this technical solution is conducive to ensuring the anti-fouling performance of the glazed tiles through the above-mentioned multi-faceted effects. It should be noted that the polishing treatment of this technology is an existing treatment method in glazed tiles, and the specific treatment method is not limited here.
[0066] Preferably, in step C, the residue of the colorful glitter glaze after passing through a 325-mesh sieve is 0.3-0.5% by mass percentage, and the glazing amount is 1.5-2.1 g / cm 2 , specific gravity is 1.28~1.32.
[0067] In order to obtain better colorful flash effect, this technical solution adjusts the fineness, glazing amount and specific gravity of the colorful flash glaze, which is beneficial to improve the quality and stability of the glazed tiles while ensuring that the glazed tiles have better colorful flash effect.
[0068] Preferably, in step C, the mesh sizes of the flash dry particles I and the flash dry particles II are both less than 100 meshes.
[0069] By limiting the mesh size of flash dry particles I and flash dry particles II, it is beneficial to reduce the processing loss of flash dry particles I and flash dry particles II and reduce the production cost of glazed tiles.
[0070] Preferably, the method further comprises step F, and step F is located before and / or after step C;
[0071] Step F specifically includes: printing color ink according to a preset pattern to form a color pattern layer.
[0072] In order to enhance the three-dimensional decorative effect of the glazed tiles in this technical solution, this technical solution can also print color ink according to a preset pattern to form a color pattern layer. It should be noted that the color pattern layer in this technical solution is printed with conventional color ink in the ceramic field, and the color ink is not further described here.
[0073] Further, in step C, the chemical composition of the flash dry particles I includes, calculated by mass percentage, Al2O3 9.8-10.1%, SiO2 3.0-3.3%, CaO 4.2-4.35%, MgO 2.8-3%, K2O 1.2-1.3%, Na2O 0.05-0.1%, TiO2 1.5-1.8%, B2O3 0.1-0.2%, BaO 23.5-24%, Li2O 3.0-3.5%, SrO 10.2-10.6%, P2O5 18-18.6%, F 18.5-19% and Y2O3 1.2-1.5%;
[0074] Calculated by mass percentage, the chemical components of the flash dry particles II include Al2O3 0.02-0.05%, Fe2O3 0.01-0.03%, CaO 0.01-0.05%, K2O 3.3-3.6%, Na2O 0.02-0.05%, TiO2 27.5-27.8%, BaO 0.05-0.1%, Li2O 0.05-0.1%, P2O5 27.2-27.6%, W 10.5-11%, Nb2O5 29.5-30% and Ta2O5 0.1-0.3%.
[0075] The technical solution preferably adds glitter dry particles I having a Y2O3 content of 1.2 to 1.5% calculated by mass percentage to the colorful glitter glaze, which is beneficial to ensure the colorful glitter effect of the glazed tiles while saving costs.
[0076] Furthermore, the present technical scheme preferably adds flashing dry particles II having a Nb2O5 content of 29.5-30% and a Ta2O5 content of 0.1-0.3% calculated by mass percentage to the colorful flashing glaze, so that the sum of the contents of Nb2O5 and Ta2O5 in the colorful flashing glaze reaches 29.6-30.3%, which is beneficial to improving the colorful flashing effect of the glazed tiles.
[0077] Furthermore, in step C, the high temperature transparent dry particles I also include transparent frit I;
[0078] Calculated by weight, the raw materials of the high-temperature transparent dry particles I include 30 to 50 parts of transparent frit I, 2 to 5 parts of flash dry particles I and 2 to 8 parts of flash dry particles II;
[0079] Calculated by weight, the raw materials of the transparent frit I include 5-10 parts of kaolin, 0-5 parts of aluminum oxide, 5-15 parts of quartz, 20-45 parts of potassium-sodium feldspar, 3-7 parts of zinc oxide, 3-10 parts of strontium carbonate, 3-7 parts of barium carbonate and 0-2 parts of lithium mica.
[0080] Since the flash dry granules I contain the rare earth component yttrium trioxide, and the flash dry granules II contain the rare earth components niobium pentoxide and tantalum pentoxide, the prices of the flash dry granules I and II are relatively high. Therefore, this technical solution further optimizes the raw material ratio of the high-temperature transparent dry granules I, so that the addition amount of the flash dry granules I and the flash dry granules II is relatively small, which is conducive to ensuring the performance of the colorful flash glazed tiles under the premise of saving.
[0081] Furthermore, by adding transparent frit I to high-temperature transparent dry particles I, it is helpful to ensure the initial melting point and expansion coefficient of high-temperature transparent dry particles I, and thus ensure the performance of colorful flashing glazed tiles. In addition, the raw material composition and proportion of transparent frit I are limited so that transparent frit I can melt at high temperature and form a transparent surface, so that the colorful flashing glaze layer can present a clearer and more transparent appearance, which is helpful to ensure the appearance of glazed tiles. In addition, the raw materials such as kaolin, alumina, quartz, potassium sodium feldspar and zinc oxide in transparent frit I can form a silicate network structure after high-temperature calcination. The above silicate network structure can enhance hardness and wear resistance, which is helpful to improve the durability and service life of glazed tiles.
[0082] Furthermore, in step C, calculated by weight, the raw materials of the low-temperature transparent dry particles I include 1 to 3 parts of kaolin, 5 to 7 parts of quartz, 20 to 45 parts of potassium-sodium feldspar, 6 to 13 parts of zinc oxide, 10 to 35 parts of sodium bicarbonate, 3 to 10 parts of strontium carbonate and 5 to 20 parts of lithium mica.
[0083] This technical solution limits the types and addition amounts of raw materials in low-temperature transparent dry particles I, which is conducive to ensuring the initial melting point and expansion coefficient of low-temperature transparent dry particles I. At the same time, by adding kaolin and quartz to the formula, it is conducive to improving the strength and hardness of glazed tiles.
[0084] Furthermore, the method further comprises step E, and step E is before step C;
[0085] Step E specifically comprises: applying a flash strengthening glaze to obtain a flash strengthening glaze layer;
[0086] Calculated by weight, the raw materials of the flash enhancement glaze include high-temperature transparent dry particles II, low-temperature transparent dry particles II, zircon sand and base glaze II;
[0087] The initial melting point of the high-temperature transparent dry granules II is greater than the initial melting point of the low-temperature transparent dry granules II.
[0088] In a preferred embodiment of the present technical solution, by adding a flash-enhancing glaze layer, it is helpful to enhance the colorful flash effect of the polished glaze tile to a greater extent.
[0089] Specifically, the glassy component in the flash-enhancing glaze can form a glass phase with a refractive index of 1.54 after calcination, and the zircon sand in the flash-enhancing glaze can also form cubic zirconium oxide crystals with a refractive index of 2.14 after high-temperature calcination. The zirconium oxide crystals in the flash-enhancing glaze layer can not only undergo complex refraction, reflection and interference phenomena with the glass phase in the flash-enhancing glaze layer, but also undergo complex refraction, reflection and interference phenomena with niobium pentoxide, tantalum pentoxide and yttrium trioxide in the colorful flash glaze layer, thereby facilitating the improvement of the colorful flash effect of the polished glazed tile. In addition, since the zirconium oxide crystals in the flash-enhancing glaze layer and the niobium pentoxide, tantalum pentoxide and yttrium trioxide crystals in the colorful flash glaze layer are respectively located in different glaze layers, that is, the flash points in the polished glazed tile are distributed in different glaze layers, it is not only conducive to enhancing the three-dimensional sense and layered sense of the flash points, but also conducive to producing more complex and varied light and shadow effects, thereby greatly improving the colorful flash effect.
[0090] More specifically, in the present technical solution, the initial melting point of the high-temperature transparent dry particles II is different from the initial melting point of the low-temperature transparent dry particles II. By adjusting the ratio of the above two transparent dry particles, the calcination temperature of the flash-enhancing glaze can be flexibly adjusted, thereby achieving the adjustability of the calcination temperature of the polished glaze bricks, providing greater flexibility and precision for production.
[0091] Preferably, in step E, according to mass percentage, the residue of the flash enhancement glaze after passing through a 325-mesh sieve is 0.3-0.5%, and the glazing amount is 1.42-1.9 g / cm 2 , specific gravity is 1.2~1.25.
[0092] In order to obtain better colorful flash effects, this technical solution adjusts the fineness, glazing amount and specific gravity of the flash enhancing glaze, which is beneficial to improve the quality and stability of the glazed tiles while ensuring that the glazed tiles have better colorful flash effects.
[0093] Further, in step E, the flash enhancement glaze includes 10 to 30 parts of high temperature transparent dry particles II, 10 to 30 parts of low temperature transparent dry particles II, 20 to 70 parts of zircon sand and 10 to 50 parts of base glaze II, calculated by weight;
[0094] The expansion coefficient of the base glaze II is (270-280)×10 -6 / ℃;
[0095] The high temperature transparent dry granules II have an initial melting point of 1000-1080°C and an expansion coefficient of (230-250)×10 -6 / ℃;
[0096] The low-temperature transparent dry granules II have an initial melting point of 900-950°C and an expansion coefficient of (205-220)×10 -6 / ℃.
[0097] This technical solution limits the amount of zircon sand added to the flash-enhancing glaze, so that there is a difference in refractive index between the flash-enhancing glaze layer and the colorful flash glaze layer. When light passes through, multiple refractions and reflections will occur on the two glaze layers with different refractive indices, thereby producing a more complex, varied and layered light and shadow effect, which is beneficial to improving the colorful flash effect of polished glazed tiles.
[0098] Furthermore, there are also significant differences in expansion coefficients between base glaze II, high temperature transparent dry particles II, and low temperature transparent dry particles II and zircon sand. During the calcination process of polished glaze tiles, the above differences are also conducive to enhancing the colorful flash effect of polished glaze tiles. In addition, by limiting the expansion coefficients of base glaze II, high temperature transparent dry particles II, and low temperature transparent dry particles II and their addition amounts, the expansion coefficient of the flash enhanced glaze layer obtained after the flash enhanced glaze is calcined is (190~210)×10 -6 / ℃, the expansion coefficient matching between the flash strengthening glaze layer and other glaze layers is enhanced, which is beneficial to increase the flatness of the polished glaze tile. In addition, since the expansion coefficient of the flash strengthening glaze layer is also lower than that of the body layer, it is also beneficial to enhance the strength, hardness and flatness of the polished glaze tile.
[0099] Furthermore, in step C and step E, calculated by weight, the raw materials of the base glaze I and the base glaze II include 5-10 parts of raw kaolin, 3-7 parts of burned kaolin, 2-5 parts of burned zinc oxide, 1-10 parts of wollastonite, 2-7 parts of calcite, 1-5 parts of dolomite, 0-5 parts of burned talc, 1-9 parts of quartz and 0-6 parts of strontium carbonate.
[0100] This technical solution is conducive to ensuring the expansion coefficient of base glaze I and base glaze II by limiting the raw material composition and raw material ratio of base glaze I and base glaze II. In addition, both raw kaolin and burned kaolin are rich in chemical components such as aluminum oxide and silicon dioxide that are conducive to improving hardness. Quartz, calcite and wollastonite are also conducive to improving hardness. The mutual coordination of the above raw materials is conducive to giving base glaze I and base glaze II a higher hardness, thereby helping to improve the hardness of colorful flash polished glaze tiles.
[0101] Further, in step E, calculated by weight, the high-temperature transparent dry particles II include 1 to 7 parts of kaolin, 3 to 7 parts of aluminum oxide, 5 to 15 parts of quartz, 20 to 45 parts of potassium-sodium feldspar, 3 to 7 parts of zinc oxide, 0 to 10 parts of sodium bicarbonate, 3 to 10 parts of strontium carbonate, 0 to 7 parts of barium carbonate and 0 to 5 parts of lithium mica.
[0102] This technical solution limits the types and addition amounts of raw materials in high temperature transparent dry granules II, which is conducive to ensuring the initial melting point and expansion coefficient of high temperature transparent dry granules II. At the same time, by adding kaolin, alumina and quartz to the formula, it is conducive to improving the strength and hardness of glazed tiles.
[0103] Furthermore, in step E, the low-temperature transparent dry particles II include 50 to 90 parts of transparent frit II and 10 to 50 parts of high-lead frit, calculated by weight;
[0104] Calculated by weight, the raw materials of the transparent frit II include 1-3 parts of kaolin, 0-1 parts of aluminum oxide, 3-7 parts of quartz, 20-45 parts of potassium-sodium feldspar, 3-7 parts of zinc oxide, 3-15 parts of sodium bicarbonate, 3-10 parts of strontium carbonate, 0-3 parts of barium carbonate and 2-7 parts of lithium mica;
[0105] Calculated by weight, the raw materials of the high-lead frit include 33 to 75 parts of lead oxide and 25 to 67 parts of quartz.
[0106] Since the initial melting point of the high-lead frit is relatively low, the technical solution adds high-lead frit to the low-temperature transparent dry particles II and limits the amount of high-lead frit added, which is conducive to making the low-temperature transparent dry particles II have a lower initial melting point. In addition, the raw materials of the high-lead frit include lead oxide and quartz. Lead oxide and quartz react to form lead silicate with a refractive index of 2.01, and lead silicate and zirconium oxide, niobium pentoxide, tantalum pentoxide and yttrium trioxide in the glaze layer undergo complex refraction, reflection and interference phenomena, which are also conducive to improving the colorful flash effect of glazed tiles. In addition, the technical solution limits the amount of lead oxide and quartz added to the high-lead frit, making the high-lead frit basically non-toxic. According to the standard "GB / T3810.15-2016 Ceramic Tile Test Method Part 15: Determination of Lead and Cadmium Dissolution from Glazed Tiles", the lead dissolution of glazed tiles is <0.003mg / dm 2 , in line with national standards.
[0107] A colorful flashing glaze-polished tile is prepared by using the method for preparing the colorful flashing glaze-polished tile.
[0108] This technical solution also proposes a colorful flashing glaze tile, which, while ensuring the adjustable calcination temperature and flatness, can not only present a strong colorful flashing effect, but also has high hardness and anti-fouling performance, combining decorativeness and practicality, which is conducive to meeting the use needs of consumers.
[0109] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0110] Example 1
[0111] A. Prepare ceramic blanks, press the ceramic blanks, and obtain a blank layer after drying; the expansion coefficient of the blank layer is 220×10 -6 / ℃, the green body layer is prepared from conventional green body raw materials in the ceramic field, and the chemical composition of the green body layer includes SiO267.85%, Al2O317.23%, Fe2O31.42%, TiO20.23%, CaO 1.18%, MgO1.65%, K2O 1.85%, Na2O 2.05% and ignition loss 4.3% according to mass percentage;
[0112] B. Apply the base glaze to obtain the base glaze layer; the expansion coefficient of the base glaze layer is 240×10 -6 / ℃, the bottom glaze layer is fired by conventional bottom glaze in the ceramic field, and the chemical composition of the bottom glaze layer includes Al2O316.73%, SiO250.48%, CaO 8.04%, MgO 5.79%, BaO 7.01%, ZnO 4.85%, K2O 3.9% and Na2O3.03% according to mass percentage;
[0113] C. Apply colorful glitter glaze to obtain a colorful glitter glaze layer; calculated by weight, the raw materials of the colorful glitter glaze include 10 parts of high-temperature transparent dry particles I, 10 parts of low-temperature transparent dry particles I, 5 parts of zircon sand and 20 parts of base glaze I; calculated by weight, the raw materials of base glaze I include 5 parts of raw kaolin, 7 parts of burned kaolin, 2 parts of burned zinc oxide, 2 parts of wollastonite, 4 parts of calcite, 3 parts of dolomite, 2 parts of burned talc, 2 parts of quartz and 1 part of strontium carbonate, and the expansion coefficient of base glaze I is 273×10 -6 / ℃; calculated by weight, the raw materials of high temperature transparent dry granules I include 30 parts of transparent frit I, 5 parts of flash dry granules I and 2 parts of flash dry granules II, and the melting point of high temperature transparent dry granules I is 1030℃, and the expansion coefficient is 228×10 -6 / ℃; calculated by mass, the transparent frit I includes 5 parts of kaolin, 2 parts of alumina, 5 parts of quartz, 20 parts of potassium-sodium feldspar, 3 parts of zinc oxide, 3 parts of strontium carbonate, 3 parts of barium carbonate and 1 part of lithium mica; calculated by mass percentage, the chemical components of the flash dry particles I include Al2O310.02%, SiO23.29%, CaO4.32%, MgO 2.95%, K2O 1.27%, Na2O 0.05%, TiO21.60%, B2O30.16%, BaO 23.68%, Li2O 3.2%, SrO 10.59%, P2O518.5%, F18.89% and Y2O31.48%; calculated by mass percentage, the chemical components of the flash dry particles II include Al2O30.02%, Fe2O30.01%, CaO 0.01%, K2O 3.56%, Na2O 0.02%, TiO2 27.72%, BaO 0.05%, Li2O 0.08%, P2O5 27.6%, W 10.85%, Nb2O5 29.96% and Ta2O5 0.12%; calculated by weight, the raw materials of low-temperature transparent dry particles I include 2 parts of kaolin, 5 parts of quartz, 20 parts of potassium-sodium feldspar, 8 parts of zinc oxide, 10 parts of sodium bicarbonate, 3 parts of strontium carbonate and 10 parts of lithium mica, and the initial melting point of low-temperature transparent dry particles I is 900℃, and the expansion coefficient is 210×10 -6 / ℃;
[0114] D. After drying, it is put into the kiln for firing. After polishing, colorful flashing glazed tiles are obtained. The surface effect is as follows Figure 1 shown.
[0115] Example 2
[0116] A. Prepare ceramic blanks, press the ceramic blanks, and obtain a blank layer after drying; the expansion coefficient of the blank layer is 220×10 -6 / ℃, the green body layer is prepared from conventional green body raw materials in the ceramic field, and the chemical composition of the green body layer includes SiO267.85%, Al2O317.23%, Fe2O31.42%, TiO20.23%, CaO 1.18%, MgO1.65%, K2O 1.85%, Na2O 2.05% and ignition loss 4.3% according to mass percentage;
[0117] B. Apply the base glaze to obtain the base glaze layer; the expansion coefficient of the base glaze layer is 240×10 -6 / ℃, the bottom glaze layer is fired by conventional bottom glaze in the ceramic field, and the chemical composition of the bottom glaze layer includes Al2O316.73%, SiO250.48%, CaO 8.04%, MgO 5.79%, BaO 7.01%, ZnO 4.85%, K2O 3.9% and Na2O3.03% according to mass percentage;
[0118] E. Applying a flash strengthening glaze to obtain a flash strengthening glaze layer; wherein, calculated by weight, the flash strengthening glaze comprises 20 parts of high temperature transparent dry particles II, 20 parts of low temperature transparent dry particles II, 30 parts of zircon sand and 30 parts of base glaze II; calculated by weight, the raw materials of base glaze II include 8 parts of raw kaolin, 4 parts of burnt kaolin, 3 parts of burnt zinc oxide, 2 parts of wollastonite, 4 parts of calcite, 2 parts of dolomite, 1 part of burnt talc, 3 parts of quartz and 1 part of strontium carbonate, and the expansion coefficient of base glaze II is 275×10 -6 / ℃; calculated by weight, the high temperature transparent dry granules II include 2 parts of kaolin, 4 parts of aluminum oxide, 10 parts of quartz, 30 parts of potassium sodium feldspar, 4 parts of zinc oxide, 3 parts of sodium bicarbonate, 4 parts of strontium carbonate, 2 parts of barium carbonate and 1 part of lithium mica, and the initial melting point of the high temperature transparent dry granules II is 1020℃, and the expansion coefficient is 241×10 -6 / ℃; calculated by weight, low-temperature transparent dry granules II include 60 parts of transparent frit II and 40 parts of high-lead frit, and the initial melting point of low-temperature transparent dry granules II is 915℃, and the expansion coefficient is 208×10 -6 / ℃; calculated by weight, the raw materials of transparent frit II include 2 parts of kaolin, 0.5 parts of aluminum oxide, 4 parts of quartz, 25 parts of potassium sodium feldspar, 4 parts of zinc oxide, 10 parts of sodium bicarbonate, 7 parts of strontium carbonate, 1 part of barium carbonate and 5 parts of lithium mica; calculated by weight, the raw materials of high-lead frit include 40 parts of lead oxide and 50 parts of quartz;
[0119] C. Apply colorful glitter glaze to obtain a colorful glitter glaze layer; calculated by weight, the raw materials of the colorful glitter glaze include 20 parts of high-temperature transparent dry particles I, 15 parts of low-temperature transparent dry particles I, 8 parts of zircon sand and 20 parts of base glaze I; calculated by weight, the raw materials of base glaze I include 10 parts of raw kaolin, 5 parts of burned kaolin, 3 parts of burned zinc oxide, 2 parts of wollastonite, 4 parts of calcite, 2 parts of dolomite, 1 part of burned talc, 3 parts of quartz and 2 parts of strontium carbonate, and the expansion coefficient of base glaze I is 275×10 -6 / ℃; calculated by weight, the raw materials of high temperature transparent dry granules I include 30 parts of transparent frit I, 5 parts of flash dry granules I and 3 parts of flash dry granules II, and the melting point of high temperature transparent dry granules I is 1020℃, and the expansion coefficient is 227×10 -6 / ℃; calculated by mass, the raw materials of transparent frit I include 6 parts of kaolin, 2 parts of alumina, 10 parts of quartz, 30 parts of potassium-sodium feldspar, 4 parts of zinc oxide, 8 parts of strontium carbonate, 3 parts of barium carbonate and 1 part of lithium mica; calculated by mass percentage, the chemical components of flash dry particles I include Al2O310.02%, SiO23.29%, CaO 4.32%, MgO 2.95%, K2O 1.27%, Na2O 0.05%, TiO21.60%, B2O30.16%, BaO23.68%, Li2O 3.2%, SrO 10.59%, P2O518.5%, F18.89% and Y2O31.48%; calculated by mass percentage, the chemical components of flash dry particles II include Al2O30.02%, Fe2O30.01%, CaO 0.01%, K2O 3.56%, Na2O 0.02%, TiO2 27.72%, BaO 0.05%, Li2O 0.08%, P2O5 27.6%, W 10.85%, Nb2O5 29.96% and Ta2O5 0.12%; calculated by weight, the raw materials of low-temperature transparent dry particles I include 2 parts of kaolin, 6 parts of quartz, 30 parts of potassium-sodium feldspar, 8 parts of zinc oxide, 20 parts of sodium bicarbonate, 5 parts of strontium carbonate and 7 parts of lithium mica, and the initial melting point of low-temperature transparent dry particles I is 930℃, and the expansion coefficient is 216×10 -6 / ℃;
[0120] D. After drying, it is put into the kiln for firing, and after polishing, colorful and shiny glazed tiles are obtained.
[0121] Example 3
[0122] A. Prepare ceramic blanks, press the ceramic blanks, and obtain a blank layer after drying; the expansion coefficient of the blank layer is 220×10 -6 / ℃, the green body layer is prepared from conventional green body raw materials in the ceramic field, and the chemical composition of the green body layer includes SiO267.85%, Al2O317.23%, Fe2O31.42%, TiO20.23%, CaO 1.18%, MgO1.65%, K2O 1.85%, Na2O 2.05% and ignition loss 4.3% according to mass percentage;
[0123] B. Apply the base glaze to obtain the base glaze layer; the expansion coefficient of the base glaze layer is 240×10 -6 / ℃, the bottom glaze layer is fired by conventional bottom glaze in the ceramic field, and the chemical composition of the bottom glaze layer includes Al2O316.73%, SiO250.48%, CaO 8.04%, MgO 5.79%, BaO 7.01%, ZnO 4.85%, K2O 3.9% and Na2O3.03% according to mass percentage;
[0124] E. Applying a flash strengthening glaze to obtain a flash strengthening glaze layer; wherein, calculated by weight, the flash strengthening glaze includes 10 parts of high temperature transparent dry particles II, 15 parts of low temperature transparent dry particles II, 35 parts of zircon sand and 15 parts of base glaze II; calculated by weight, the raw materials of base glaze II include 8 parts of raw kaolin, 4 parts of burnt kaolin, 4 parts of burnt zinc oxide, 3 parts of wollastonite, 4 parts of calcite, 2 parts of dolomite, 1 part of burnt talc, 4 parts of quartz and 2 parts of strontium carbonate, and the expansion coefficient of base glaze II is 276×10 -6 / ℃; calculated by weight, the high temperature transparent dry granules II include 2 parts of kaolin, 6 parts of aluminum oxide, 13 parts of quartz, 38 parts of potassium sodium feldspar, 4 parts of zinc oxide, 3 parts of sodium bicarbonate, 6 parts of strontium carbonate, 2 parts of barium carbonate and 3 parts of lithium mica, and the initial melting point of the high temperature transparent dry granules II is 1035℃, and the expansion coefficient is 242×10 -6 / ℃; calculated by weight, low-temperature transparent dry granules II include 90 parts of transparent frit II and 10 parts of high-lead frit, and the initial melting point of low-temperature transparent dry granules II is 900℃, and the expansion coefficient is 208×10 -6 / ℃; calculated by weight, the raw materials of transparent frit II include 2 parts of kaolin, 1 part of aluminum oxide, 4 parts of quartz, 28 parts of potassium sodium feldspar, 5 parts of zinc oxide, 4 parts of sodium bicarbonate, 5 parts of strontium carbonate, 2 parts of barium carbonate and 3 parts of lithium mica; calculated by weight, the raw materials of high-lead frit include 45 parts of lead oxide and 55 parts of quartz;
[0125] C. Apply colorful glitter glaze to obtain a colorful glitter glaze layer; calculated by weight, the raw materials of the colorful glitter glaze include 20 parts of high-temperature transparent dry particles I, 15 parts of low-temperature transparent dry particles I, 8 parts of zircon sand and 24 parts of base glaze I; calculated by weight, the raw materials of base glaze I include 8 parts of raw kaolin, 4 parts of burned kaolin, 3 parts of burned zinc oxide, 5 parts of wollastonite, 4 parts of calcite, 3 parts of dolomite, 2 parts of burned talc, 6 parts of quartz and 3 parts of strontium carbonate, and the expansion coefficient of base glaze I is 276×10 -6 / ℃; calculated by weight, the raw materials of high temperature transparent dry granules I include 30 parts of transparent frit I, 3 parts of flash dry granules I and 4 parts of flash dry granules II, and the melting point of high temperature transparent dry granules I is 1030℃, and the expansion coefficient is 227×10 -6 / ℃; calculated by weight, the raw materials of transparent frit I include 6 parts of kaolin, 3 parts of alumina, 8 parts of quartz, 35 parts of potassium-sodium feldspar, 6 parts of zinc oxide, 4 parts of strontium carbonate, 4 parts of barium carbonate and 1 part of lithium mica; calculated by weight percentage, the chemical components of flash dry particles I include Al2O310.02%, SiO23.29%, CaO 4.32%, MgO 2.95%, K2O 1.27%, Na2O 0.05%, TiO21.60%, B2O30.16%, BaO 23.68%, Li2O3.2%, SrO 10.59%, P2O518.5%, F18.89% and Y2O31.48%; calculated by weight percentage, the chemical components of flash dry particles II include Al2O30.02%, Fe2O30.01%, CaO 0.01%, K2O 3.56%, Na2O 0.02%, TiO2 27.72%, BaO 0.05%, Li2O 0.08%, P2O5 27.6%, W 10.85%, Nb2O5 29.96% and Ta2O5 0.12%; calculated by weight, the raw materials of low-temperature transparent dry particles I include 2 parts of kaolin, 4 parts of quartz, 29 parts of potassium-sodium feldspar, 7 parts of zinc oxide, 28 parts of sodium bicarbonate, 6 parts of strontium carbonate and 15 parts of lithium mica, and the initial melting point of low-temperature transparent dry particles I is 932℃, and the expansion coefficient is 213×10 -6 / ℃;
[0126] D. After drying, it is put into the kiln for firing, and after polishing, colorful and shiny glazed tiles are obtained.
[0127] Comparative Example 1
[0128] The preparation method and raw materials of Comparative Example 1 are the same as those of Example 2, except that the high-temperature transparent dry particles I are not added to the colorful glitter glaze of Comparative Example 1.
[0129] Comparative Example 2
[0130] The preparation method and raw materials of Comparative Example 2 are the same as those of Example 2, except that the low-temperature transparent dry particles I are not added to the colorful glitter glaze of Comparative Example 2.
[0131] Comparative Example 3
[0132] The preparation method and raw materials of Comparative Example 3 are the same as those of Example 2, except that zircon sand is not added to the colorful glitter glaze of Comparative Example 3.
[0133] The polished glazed tiles prepared in the embodiment and the comparative example were respectively subjected to conventional hardness and antifouling grade tests in the field of architectural ceramics technology, and the morphology and surface effect of the polished glazed tiles were observed. The results are shown in Table 1 below:
[0134]
[0135] It can be seen from the performance test results in Table 1 that the glazed tiles obtained by this technical solution can not only present a strong colorful flashing effect while ensuring flatness, but also have high hardness and anti-fouling performance, combining decorativeness and practicality, which is conducive to meeting the use needs of consumers.
[0136] In Comparative Example 1, since high-temperature transparent dry particles I are not added, not only does it result in no precipitation of niobium pentoxide, tantalum pentoxide and yttrium trioxide crystals in the colorful flashing glaze layer, but it also results in the inability to utilize the difference in expansion coefficients between high-temperature transparent dry particles I and zircon sand, which reduces the number of microcracks formed in the glaze layer, thereby weakening the colorful flashing effect on the surface. Although the surface still has a colorful flashing effect, compared with the colorful flashing effect of Example 2, the colorful flashing effect of the glazed tiles obtained in Comparative Example 1 is weaker.
[0137] In Comparative Example 2, since low-temperature transparent dry particles I are not added, the difference in expansion coefficients between low-temperature transparent dry particles I and zircon sand cannot be utilized, so that the microcracks formed in the glaze layer are reduced, thereby weakening the colorful flash effect on the surface. Although the surface still has a colorful flash effect, compared with the colorful flash effect of Example 2, the colorful flash effect of the glazed tiles obtained in Comparative Example 2 is average.
[0138] In Comparative Example 3, since zircon sand is not added, there is no precipitation of cubic zirconia crystals in the colorful flashing glaze layer, and it is also impossible to utilize the difference in expansion coefficients between the base glaze I, high-temperature transparent dry particles I, and low-temperature transparent dry particles I and zircon sand, so that very few microcracks are formed in the colorful flashing glaze layer, thereby weakening the colorful flashing effect on the surface. Although the surface still has a colorful flashing effect, compared with the colorful flashing effect of Example 2, the colorful flashing effect of the glazed tiles obtained in Comparative Example 3 is weaker.
[0139] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. A method for preparing colorful flashing glazed tiles, characterized in that: The following steps are involved: A. Prepare a ceramic blank, press the ceramic blank, and obtain a blank layer after drying; the expansion coefficient of the blank layer is (215-240)×10 -6 / ℃; B. Applying the base glaze to obtain a base glaze layer; the expansion coefficient of the base glaze layer is (220-250)×10 -6 / ℃; E. Applying flash strengthening glaze to obtain a flash strengthening glaze layer; Calculated by weight, the flash enhancement glaze includes 10 to 30 parts of high-temperature transparent dry particles II, 10 to 30 parts of low-temperature transparent dry particles II, 20 to 70 parts of zircon sand and 10 to 50 parts of base glaze II; The expansion coefficient of the base glaze II is (270-280)×10 -6 / ℃, and calculated by weight, the raw materials of the base glaze II include 5-10 parts of raw kaolin, 3-7 parts of burned kaolin, 2-5 parts of burned zinc oxide, 1-10 parts of wollastonite, 2-7 parts of calcite, 1-5 parts of dolomite, 0-5 parts of burned talc, 1-9 parts of quartz and 0-6 parts of strontium carbonate; The high temperature transparent dry granules II have an initial melting point of 1000-1080°C and an expansion coefficient of (230-250)×10 -6 / ℃; The low-temperature transparent dry granules II have an initial melting point of 900-950°C and an expansion coefficient of (205-220)×10 -6 / ℃; Calculated by weight, the low-temperature transparent dry granules II include 50 to 90 parts of transparent frit II and 10 to 50 parts of high-lead frit; Calculated by weight, the raw materials of the transparent frit II include 1-3 parts of kaolin, 0-1 parts of aluminum oxide, 3-7 parts of quartz, 20-45 parts of potassium-sodium feldspar, 3-7 parts of zinc oxide, 3-15 parts of sodium bicarbonate, 3-10 parts of strontium carbonate, 0-3 parts of barium carbonate and 2-7 parts of lithium mica; Calculated by weight, the raw materials of the high-lead frit include 33 to 75 parts of lead oxide and 25 to 67 parts of quartz; C. applying colorful glitter glaze to obtain a colorful glitter glaze layer; Calculated by weight, the raw materials of the colorful flashing glaze include 10-50 parts of high-temperature transparent dry particles I, 10-50 parts of low-temperature transparent dry particles I, 5-10 parts of zircon sand and 10-50 parts of base glaze I; The expansion coefficient of the base glaze I is (270-280)×10 -6 / ℃, and calculated by weight, the raw materials of the base glaze I include 5-10 parts of raw kaolin, 3-7 parts of burned kaolin, 2-5 parts of burned zinc oxide, 1-10 parts of wollastonite, 2-7 parts of calcite, 1-5 parts of dolomite, 0-5 parts of burned talc, 1-9 parts of quartz and 0-6 parts of strontium carbonate; The low-temperature transparent dry particles I have an initial melting point of 900-950°C and an expansion coefficient of (210-220)×10 -6 / ℃; The high temperature transparent dry particles I have an initial melting point of 1000-1080°C and an expansion coefficient of (225-235)×10 -6 / ℃; The raw materials of the high temperature transparent dry particles I include flash dry particles I and flash dry particles II, and the chemical composition of the flash dry particles I includes yttrium trioxide, and the chemical composition of the flash dry particles II includes niobium pentoxide and tantalum pentoxide; D. After drying, it is put into the kiln for firing, and after polishing, colorful and shiny glazed tiles are obtained.
2. The method for preparing a colorful flashing glaze tile according to claim 1, characterized in that: In step C, the chemical composition of the flash dry particles I includes, calculated by mass percentage, Al2O3 9.8-10.1%, SiO2 3.0-3.3%, CaO 4.2-4.35%, MgO 2.8-3%, K2O 1.2-1.3%, Na2O 0.05-0.1%, TiO2 1.5-1.8%, B2O3 0.1-0.2%, BaO 23.5-24%, Li2O 3.0-3.5%, SrO 10.2-10.6%, P2O5 18-18.6%, F 18.5-19% and Y2O3 1.2-1.5%; Calculated by mass percentage, the chemical components of the flash dry particles II include Al2O3 0.02-0.05%, Fe2O3 0.01-0.03%, CaO 0.01-0.05%, K2O 3.3-3.6%, Na2O 0.02-0.05%, TiO2 27.5-27.8%, BaO 0.05-0.1%, Li2O 0.05-0.1%, P2O5 27.2-27.6%, W 10.5-11%, Nb2O5 29.5-30% and Ta2O5 0.1-0.3%.
3. The method for preparing a colorful flashing glaze tile according to claim 1, characterized in that: In step C, the high temperature transparent dry particles I further include transparent frit I; Calculated by weight, the raw materials of the high-temperature transparent dry particles I include 30 to 50 parts of transparent frit I, 2 to 5 parts of flash dry particles I and 2 to 8 parts of flash dry particles II; Calculated by weight, the raw materials of the transparent frit I include 5-10 parts of kaolin, 0-5 parts of aluminum oxide, 5-15 parts of quartz, 20-45 parts of potassium-sodium feldspar, 3-7 parts of zinc oxide, 3-10 parts of strontium carbonate, 3-7 parts of barium carbonate and 0-2 parts of lithium mica.
4. The method for preparing a colorful flashing glaze tile according to claim 1, characterized in that: In step C, calculated by weight, the raw materials of the low-temperature transparent dry particles I include 1 to 3 parts of kaolin, 5 to 7 parts of quartz, 20 to 45 parts of potassium-sodium feldspar, 6 to 13 parts of zinc oxide, 10 to 35 parts of sodium bicarbonate, 3 to 10 parts of strontium carbonate and 5 to 20 parts of lithium mica.
5. The method for preparing a colorful flashing glaze-polished tile according to claim 1, characterized in that: In step E, calculated by weight, the high-temperature transparent dry particles II include 1 to 7 parts of kaolin, 3 to 7 parts of aluminum oxide, 5 to 15 parts of quartz, 20 to 45 parts of potassium-sodium feldspar, 3 to 7 parts of zinc oxide, 0 to 10 parts of sodium bicarbonate, 3 to 10 parts of strontium carbonate, 0 to 7 parts of barium carbonate and 0 to 5 parts of lithium mica.
6. A colorful flashing glazed tile, characterized in that: The colorful flashing glazed brick is prepared by the preparation method of any one of claims 1 to 5.
Citation Information
Patent Citations
Wear-resistant antifouling ceramic starlight glazed brick and preparation method thereof
CN112979349A
Ceramic tile with ice crack and flash effects and preparation method thereof
CN116813387A